Effective Delivery of siRNA-Loaded Nanoparticles for Overcoming Oxaliplatin Resistance in Colorectal Cancer - Zhou, Yue; Zhang, Qing; Wang, Minjia; Huang, Chengzhi; Yao, Xueqing (Frontiers in Oncology, 2022)
Chemotherapy resistance represents a formidable obstacle in advanced or metastatic colorectal cancer (CRC) patients. It is reported that ATPase copper transporting alpha (ATP7A) plays an important role in chemotherapy resistance in CRC. Here, we identified ATP7A as a potentially key gene of OXA resistance in CRC. The patients with higher expression of ATP7A tended to have platinum drug resistance. While the lower expression of ATP7A by siRNA knockdown resulted in enhancement of OXA sensitivity and increased OXA-induced apoptosis. Further, we demonstrated a novel and safe strategy to increase CRC chemosensitivity by delivering siRNA into tumor cells via a novel nanoparticle, DAN. In summary, our study provided a novel nanocarrier-based delivery of ATP7A to interfere in a key gene of chemo-resistance in CRC, which may be a novel therapeutic strategy to overcome chemotherapy resistance in CRC.